A mixed FDTD-integral equation approach for on-site safety assessment in complex electromagnetic environments. - Lazzi, G. (IEEE Transactions on antennas and propagation)
A mixed finite-difference time-domain (FDTD)-integral equation approach for the evaluation of the power deposition in the human body model immersed in a complex electromagnetic environment is proposed. The advantage of the proposed approach is that safety assessment for exposure to generic sources may be performed on-site, in a few minutes, with high accuracy and without the need of a high-power workstation. The method uses previously stored FDTD-computed impulse responses (Green's functions) of the human body model by integrating them with the complex incident electromagnetic field distribution that can be measured on site. The application of this method to the dosimetry of cellular telephone base station antennas is presented to show its versatility and ease of use